2021
DOI: 10.1155/2021/2169431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Sternal Closure Techniques Based on Risk Factors: A Prospective, Observational Study

Abstract: Background. Stainless steel wires are still commonly used as a sternum closure technique. However, it can cause fatal complications due to rupture and dehiscence. It was anticipated that the sternal Cable System (Pioneer Surgical Technology Inc., Marquette, MI, USA) could provide a better sternal fixation and reduce the possible complications. Materials and Method. A total of 100 patients (57 male, 43 female) at high risk of dehiscence were included in this prospective observational study. Among those with Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…After median sternotomies in adults, studies of sternal dehiscence showed that BMI was also a signifcant predictor. Nevertheless, the efect of BMI in adults was refected in the negative efect of obesity [17]. Te study by Zura et al…”
Section: Discussionmentioning
confidence: 97%
“…After median sternotomies in adults, studies of sternal dehiscence showed that BMI was also a signifcant predictor. Nevertheless, the efect of BMI in adults was refected in the negative efect of obesity [17]. Te study by Zura et al…”
Section: Discussionmentioning
confidence: 97%
“…In turn, mortality due to sternal instability used to reach 50%, but medical progress and the development of new technologies have contributed to a signi cant reduction to about 10%, which is still a serious problem (15)(16). In addition, the development of these complications is in uenced by many risk factors related to patient's comorbidities, such as obesity, osteoporosis, heart failure, as well as his lifestyle and the surgery performed (4,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, mortality due to sternal instability used to reach 50%, but medical progress and the development of new technologies have contributed to a significant reduction to about 10%, which is still a serious problem 15 , 16 . In addition, the development of these complications is influenced by many risk factors associated with the patient's comorbidities, such as obesity, osteoporosis, heart failure, as well as his lifestyle and the surgery performed 4 , 14 , 17 .…”
Section: Introductionmentioning
confidence: 99%